Atrial fibrillation as a new prognosis factor in chronic patients after hospitalization: the CHRONIBERIA index - Javier Suarez-Dono; Ignacio Novo-Veleiro; Francisco Gude-Sampedro; Ricardo Marinho; Sara Xavier-Pires; Diana Rocha; João Araújo-Correia; Cecília Moreira; Francisca Beires; Danay Pérez; Filipa David; J. Vasco-Barreto; et al. (Scientific Reports, 2023)
Abstract A collaborative project in different areas of Spain and Portugal was designed to find out the variables that influence the mortality after discharge and develop a prognostic model adapted to the current healthcare needs of chronic patients in an internal medicine ward. Inclusion criteria were being admitted to an Internal Medicine department and at least one chronic disease. Patients’ physical dependence was measured through Barthel index (BI). Pfeiffer test (PT) was used to establish cognitive status. We conducted logistic regression and Cox proportional hazard models to analyze the influence of those variables on one-year mortality. We also developed an external validation once decided the variables included in the index. We enrolled 1406 patients. Mean age was 79.5 (SD = 11.5) and females were 56.5%. After the follow-up period, 514 patients (36.6%) died. Five variables were identified as significantly associated with 1 year mortality: age, being male, lower BI punctuation, neoplasia and atrial fibrillation. A model with such variables was created to estimate one-year mortality risk, leading to the CHRONIBERIA. A ROC curve was made to determine the reliability of this index when applied to the global sample. An AUC of 0.72 (0.7–0.75) was obtained. The external validation of the index was successful and showed an AUC of 0.73 (0.67–0.79). Atrial fibrillation along with an advanced age, being male, low BI score, or an active neoplasia in chronic patients could be critical to identify high risk multiple chronic conditions patients. Together, these variables constitute the new CHRONIBERIA index.